The Impact of Listening to Music During MRI-Fusion Prostate Biopsy Procedures on Pain and Anxiety Levels: A Randomized Controlled Trial - Çağrı Coşkun; Ender Cem Bulut; Serhat Çetin; Uğur Aydın; Bora Küpeli (Scandinavian Journal of Urology)
Objective: Combined biopsy (CBx) is a combination of multiparametric magnetic resonance imaging (MpMRI)-targeted prostate biopsy (FBx) and systematic biopsy (SBx). CBx offers highly accurate diagnostic rates, but the increased number of cores taken and the longer procedure time may pose challenges in tolerability compared to traditional biopsies in terms of pain and anxiety. This situation leads to the need to evaluate pain and anxiety.